ANTHROPOLOGY DIMENSIONS AS INDEPENDENT AEROBIC ENDURANCE - Ratko Pavlović; Aleksandar Raković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Endurance as human capability is treated in two ways. Some authors define it as mobility capability, while others deny this theory. The denying of this theory lies in attitude that endurance is saturated with psychological factors (motivation) and cardio- vascular factors as well and is often identified with aero power, typical dimension of fun- ctional diagnostics. Having that in mind this research enabled the obtaining of necessary informations which could contribute to the clearing up of these uncoordinated opinions. The research included 110 student of the III year Phisical Education in East Sarajevo, male gender. Nine (9) predictors has been applied (4 variables for mobility space estima- te, 5 variables for morphology and functional space estimate) and variable used for the estimate of endurance race 1500m. Obtained results confirmed statistical significance of two functional capability variable of Harvard step test, Margarija test and mobility variable race 4x15 meters with the race results.